2008
DOI: 10.1007/s00412-008-0163-7
|View full text |Cite
|
Sign up to set email alerts
|

Intercalary heterochromatin in polytene chromosomes of Drosophila melanogaster

Abstract: Intercalary heterochromatin consists of extended chromosomal domains which are interspersed throughout the euchromatin and contain silent genetic material. These domains comprise either clusters of functionally unrelated genes or tandem gene duplications and possibly stretches of noncoding sequences. Strong repression of genetic activity means that intercalary heterochromatin displays properties that are normally attributable to classic pericentric heterochromatin: high compaction, late replication and underre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 54 publications
1
32
0
Order By: Relevance
“…Heterochromatin is also associated with a number of repressive covalent modifications of histone tails (Grewal and Elgin, 2007). At least two mechanisms are responsible for the highly compact state of heterochromatin: pericentric heterochromatin is dependent on heterochromatin protein 1 (HP1) (Eissenberg and Elgin, 2000) and intercalary heterochromatin is dependent on the polycomb group (PcG) of proteins (Belyaeva et al, 2008;Zhimulev and Belyaeva, 2003). HP1 and Pc recognize their respective target sites with discriminating specificities.…”
Section: Introductionmentioning
confidence: 99%
“…Heterochromatin is also associated with a number of repressive covalent modifications of histone tails (Grewal and Elgin, 2007). At least two mechanisms are responsible for the highly compact state of heterochromatin: pericentric heterochromatin is dependent on heterochromatin protein 1 (HP1) (Eissenberg and Elgin, 2000) and intercalary heterochromatin is dependent on the polycomb group (PcG) of proteins (Belyaeva et al, 2008;Zhimulev and Belyaeva, 2003). HP1 and Pc recognize their respective target sites with discriminating specificities.…”
Section: Introductionmentioning
confidence: 99%
“…There are previously described regions of intercalary heterochromatin in all D. melanogaster euchromatic arms (Belyaeva et al 2008) that could be responsible for the H3K9me2-enriched domains found in all cell types and tissues. Comparing regions of intercalary heterochromatin with the positions of the H3K9me2-enriched domains, we find that only one of 23 regions coincide with intercalary heterochromatin identified by polytene chromosome analysis (Semeshin et al 2001), and six of 23 regions overlap with intercalary heterochromatin defined by ChIP-chip mapping of the SUUR protein (Belyakin et al 2005).…”
Section: The 4th Chromosome Is Enriched For Specialized Heterochromatmentioning
confidence: 99%
“…In the best-studied system, the Drosophila larval salivary gland (Fig. 1A), late-replicating euchromatic regions (''intercalary heterochromatin'') also underreplicate to varying degrees (for review, see Spradling and OrrWeaver 1987;Belyaeva et al 2008). Thirty to 52 underreplicated (UR) regions 90-570 kb in length have been precisely mapped using DNA arrays (Belyakin et al 2005;Nordman et al 2011;Sher et al 2012).…”
mentioning
confidence: 99%